Low molecular mass nucleoside gelators for intra-tumoural drug delivery - Skilling, Kathryn J. (2016)
There are numerous chemotherapeutic agents available today that treat a wide array of tumours. The majority of these compounds are administered via intravenous (i.v.) infusion in large doses (1000 mg/m2), necessary to sustain a desired therapeutic effect. The systemic nature of the drug delivery, the dosage size and non-specific nature of many chemotherapeutic agents however means that they attack any rapidly dividing tissue system, leading to the commonly observed side effects e.g. alopecia, nausea, neutropenia and thrombocytopenia. Low molecular weight gelators (LMWGs) are increasing in popularity as an alternative platform for drug delivery. They are typically small amphiphilic organic molecules which self-assemble in water forming a 3D gel network; they offer advantages over other drug delivery platforms as they are typically derived from biological polymers and are therefore inherently biocompatible. Using the nucleoside gemcitabine; a first-line treatment for the treatment of gastric and pancreatic cancer as a model drug, two localised delivery systems were developed. The first, an inert LMWG matrix for the encapsulation and passive release of gemcitabine and the second, a therapeutic molecular gel derived from the chemotherapeutic itself. Cytidine, an inert analogue of gemcitabine was used to develop a passive delivery system. Regioselective synthesis of N-acylated derivatives of varying chain lengths was achieved via an activated triazine ester. Using a minimal amount of ethanol and an ‘anti-solvent’ switch gelation method a gelating system derived from the N-myristoyl derivative, containing a solvent volume fraction (ΦSOL) of 0.40 was found to have the most advantageous mechanical and structural properties; a crosslinked nanofibrillar network, established by rheological measurements and microscopy (TEM). The gel was validated as a drug delivery platform via encapsulation and release low molecular weight fluorescein and high molecular weight FITC Dextran, with the gelator matrix releasing the smaller fluorescein and retarding the release of the higher molecular weight dextran. Further modification and optimisation of the passive system afforded an N-octanoyl 2’-deoxycytidine conjugate that underwent molecular reorganisation into a cross-linked nanofibrillar structure in a 100 % aqueous environment. This gel was the first of its kind to assemble in this manner and the rheological measurements demonstrate its self-healing properties, whilst encapsulation of fluorescents once again demonstrated controlled release of low molecular weight fluorescein over a 24 h period. In vitro growth inhibition assays validated the platform as biologically compatible against gastric (MKN-7) and pancreatic (MIA PaCa-2) cell lines. Additional modification of the chemotherapeutic itself laid the foundation for an intra-tumoural targeted therapeutic delivery system. Enzyme cleavable pro-drugs of gemcitabine were created with amphiphilic properties, linkages designed to undergo varying rates of hydrolysis from both the N-amino and 5ʹ-hydroxyl positions. Whilst no successful gelating entities were achieved, the N-amide and 5’-ester prodrugs were found to have comparable potencies to the parent compound in vitro when tested against gastric and pancreatic cell lines. From the results obtained during this work, it can be concluded that with further chemical modification based upon parameters discussed here on in that a LMWG system could be a viable platform for drug delivery in the future.